Can school shootings be prevented? (Academic Journal of Internal Affairs, 2011)
Analysing enriched security measures, the article focuses on long term prevention policies for school shootings. The author also provides an assessment of the opportunities and difficulties of short term interventions that are applied shortly before or after the act.
Keywords: prevention; threat; school